Individualized Responses to Ipsilesional High-Frequency and Contralesional Low-Frequency rTMS in Chronic Stroke: A Pilot Study to Support the Individualization of Neuromodulation for Rehabilitation - Kindred, John Harvey; Wonsetler, Elizabeth Carr; Charalambous, Charalambos Costas; Srivastava, Shraddha; Marebwa, Barbara Khalibinzwa; Bonilha, Leonardo; Kautz, Steven A.; Bowden, Mark G. (Frontiers in Human Neuroscience, 2020)
Background: In this pilot study we examined the effects of ipsilesional high-frequency rTMS (iHF-rTMS) and contralesional low-frequency rTMS (cLF-rTMS) applied via a double-cone coil on neurophysiological and gait variables in patients with chronic stroke. Objective/Hypothesis: To determine the group and individual level effects of two types of stimulation in order to better individualize neuromodulation for rehabilitation. Methods: Using a randomized, within-subject, double-blind, sham-controlled trial with 14 chronic stroke participants iHF-rTMS and cLF-rTMS were applied via a double-cone coil to the tibialis anterior cortical representation. Neurophysiological and gait variables were compared pre-post rTMS. Results: A small effect of cLF-rTMS indicated increased MEP amplitudes (Cohen’s D; cLF-rTMS, d=-0.30). Group-level analysis via RMANOVA showed no significant group effects of stimulation (P>0.099). However, secondary analyses of individual data showed a high degree of response variability to rTMS. Individual percent changes in resting motor threshold and normalized MEP latency correlated with changes in gait propulsive forces and walking speed (iHF-rTMS, nLAT:Pp, R=0.632 P=0.015; cLF-rTMS, rMT:SSWS, R=-0.557, P=0.039; rMT:Pp, R=0.718, P=0.004). Conclusions: Changes in propulsive forces and walking speed were seen in some individuals that showed neurophysiological changes in response to rTMS. The neurological consequences of stroke are heterogeneous making a “one type fits all” approach to neuromodulation for rehabilitation unlikely. This pilot study suggests that an individual’s unique response to rTMS should be considered prior to application/selection of neuromodulatory therapies. Before neuromodulatory therapies can be incorporated into standard clinical practice, additional work is needed to identify biomarkers of response and how best to prescribe neuromodulation for rehabilitation for post-stroke gait.